Brainstem manifestations in neuromyelitis optica: a multicenter study of 258 patients: - Kremer, Laurent; Mealy, M.; Jacob, A.; Nakashima, I.; Cabre, P.; Bigi, S.; Paul, F.; Jarius, Sven; Aktas, O.; Elsone, L.; Mutch, K.; Levy, M.; et al. (Multiple sclerosis journal, 2014)
Background: Neuromyelitis optica (NMO) is a severe autoimmune disease of the central nervous system characterized by spinal cord and optic nerve involvement. Br...
First Published October 7, 2013
Gesehen am 14.08.2020